Legal Analysis of Friedman's Justice Theory About Jointly Acquired Property in the form Songs Copyright in Indonesia - Susilo, Budhi; Kian, Antonius Maria Laot (East Asian Journal of Multidisciplinary Research, 2024)
This study's issue is how to apply Friedman's theory of justice to a lawsuit involving joint property in the form of song royalties, which is based on the Virgoun and Inara Rusli case.  This study's goal is to analyze and assess how Friedman's theory of justice applies to a case that has never happened before in Indonesia (based on Court Ruling No. 1662/Pdt.G/2023/PA.JB). In order to conduct this research, the normative method is employed. The literature review includes primary legal materials such as the Civil Code, Law No. 16 of 2019 Marriage Law Jo. Law No. 1 of 1974, Constitutional Court’s Ruling No. 69/PUU-XIII/2015, Copyright Law No. 28 of 2014, Virgoun and Inara Rusli Case Study (based on Court Ruling No. 1662/Pdt.G/2023/PA.JB). The theory of Lawrence M. Friedman states that because law is static, interference with its substance and structure happens. The external social sphere is the factor that offers input. Aspects of justice for the parties should be taken into consideration when dividing jointly acquired property. Whether or not intellectual property rights can be included in jointly acquired property does not depend on whose name the copyright is registered under. The first and most crucial thing to know is whether or not the property was acquired during a marriage.